Principles of corporate finance law. - Ferran, Eilâis; Look, Chan Ho (Oxford : Oxford University Press, 2014)
With the additional contribution of Look Chan Ho, an expert in the field of corporate finance, this thoroughly revised and updated second edition of Ferran's 'Principles of Corporate Finance Law' explores the relationship between law and finance.
Previous edition: 2008.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 24, 2014).
Keywords: Corporations -- Finance -- Law and legislation -- Great Britain